Exploring The Potential Of Integration Quality Assessment System In Construction (QLASSIC) With ISO 9001 Quality Management System (QMS) - Ali, Mukhtar Che (University of Kragujevac, Faculty of Engineering, Center for Quality, 2014)
Quality has been identified as one of the fundamental needs of clients. As such construction projects that are able to be completed with distinctive quality will definitely enable to delight their customers. In this regard, Construction Industry Development Board (CIDB) has introduced two quality related programs namely ISO 9001 DIY Scheme and QLASSIC. The later is essentially a quality performance assessment tool to evaluate the level of quality of a building construction work based on quality standards stipulated in CIS 7:2006. One of the key deliverables of QLASSIC is QLASSIC Score which denotes the level of quality of the assessed construction project. Potentially there is a strong correlation between QLASSIC and ISO 9001 QMS. However there is lack of knowledge in the industry in amalgamating QLASSIC with ISO 9001QMS towards attaining high quality performance. Indeed it is noticed that not many studies have been undertaken in this area. Thus it warrants to undertake a study that deliberates on the relationship of practicing ISO 9001QMS with the achievement of QLASSIC Score. Therefore among the key objectives of this research are generally to investigate the relationship between practicing ISO 9001 QMS principles with QLASSIC performance and to examine the expected business outcomes for ISO 9001 certified contractors that are able to sustain relatively high QLASSIC Score. Eventually it is postulated that the output of this research would enable to elevate the level of quality performance in the Malaysian construction industry.